A novel approach to characterize host cell proteins associated with therapeutic monoclonal antibodies. Issue 6 (15th February 2017) - Thomson, Andrew S.; Mai, Shing; Byrne, Michael P.
ABSTRACT: Recombinant monoclonal antibody (mAb) products are widely produced in the pharmaceutical industry using Chinese hamster ovary (CHO) cells. Host cell proteins (HCPs) are one of many process‐related impurities generated during the production of mAb products. The multi‐analyte HCP enzyme linked immunosorbent assay (ELISA) is the industry standard accepted assay to measure clearance of HCPs from recombinant protein therapeutics. While similar platform processes are used for expression and purification, varying amounts of HCPs are found in final drug substances for different mAb products. Through the use of novel ELISA formats, an HCP‐mAb product interaction was identified using a variety of ELISAs to investigate the underlying protein–protein interaction. This result provides evidence to explain why some mAb products have HCPs that are not cleared during purification. This ELISA technique can be used as a high‐throughput screening tool to identify conditions to improve clearance of difficult HCPs during downstream processing purification. In addition, an interaction was observed to occur between anti‐CHO HCP antibodies and mAb products. However, this interaction only occurs under denaturing conditions, and does not interfere with the HCP quantitation obtained by ELISA, and it was demonstrated that the cross‐reactive anti‐CHO HCP antibodies can be removed by affinity purification. Biotechnol. Bioeng. 2017;114: 1208–1214. © 2017 Wiley Periodicals, Inc.